N‐Doped InGaP Nanowire Shells in GaAs/InGaP Core–Shell p–n Junctions. Issue 2 (4th September 2019) - Liborius, Lisa; Bieniek, Jan; Nägelein, Andreas; Tegude, Franz-Josef; Prost, Werner; Hannappel, Thomas; Poloczek, Artur; Weimann, Nils
Abstract : Herein, the characterization of n‐doped InGaP:Si shells in coaxial not‐intentionally doped (nid)‐GaAs/n‐InGaP as well as n–p–n core–multishell nanowires grown by metalorganic vapor‐phase epitaxy is reported. The multi‐tip scanning tunneling microscopy technique is used for contact‐independent resistance profiling along the tapered nid‐GaAs/n‐InGaP core–shell nanowires to estimate the established emitter shell doping concentration to N D  ≈ 3 · 10 18  cm −3 . Contacts on these shells are demonstrated and exhibit ohmic current–voltage characteristics after annealing. Application potential is demonstrated by the growth and processing of coaxial p‐GaAs/n‐InGaP junctions in n–p–n core–multishell nanowires, with n‐InGaP being the electron‐supplying emitter material. Current–voltage characteristics and temperature‐dependent electroluminescence measurements substantiate successful doping of the n‐InGaP shell. A tunneling‐assisted contribution to the leakage currents of the investigated p–n junctions is verified by the sub‐bandgap luminescence at low temperatures and is attributed to radiative tunneling processes. Abstract : n‐Doped InGaP:Si nanowire shells in coaxial GaAs/InGaP core–shell and core–multishell nanowires are analyzed regarding donor concentration, ohmic contacts, as well as their implementation as electron‐supplying emitter shells in a nanowire heterojunction bipolar transistor. Multi‐tip scanning tunneling microscopy, current–voltage and electroluminescence measurements are used for the material characterization and the analysis of carrier transport mechanisms.